PERBANDINGAN METODE WEIGHTED PRODUCT DAN SIMPLE ADDITIVE WEIGHTING DALAM SELEKSI PENGURUS FORUM ASISTEN (STUDI KASUS : UNIVERSITAS AMIKOM YOGYAKARTA) - Pradana, Musthofa Galih; Kusrini, Kusrini; Luthfi, Emha Taufiq (Informasi Interaktif, 2019)
The assistant forum is an organization built by AMIKOM Yogyakarta University which serves as an official forum for Practicum Assistants. In the Forum Assistant there are daily administrators in charge of managing the daily activities of the organization. In determining the day-to-day management, a selection process is conducted, so that the elected management is the right individual and able to make the Assistant Forum organization better. Because of the importance of the selection process, a system that is able to provide recommendations to determine eligible individuals is needed. administrator. There are many methods that can be used in decision support systems, including the Weighted Product method and Simple Additive Weighting. The data of the candidates for Forum Assistant will be applied to these two methods and a comparison is made of the ranking results of the Weighted Product method and Simple Additive Weighting. The results obtained from this study are ranking from the Weighted Product method and Simple Additive Weighting which produces the same ranking of 3 data from a total of 10 data tested or similarity percentage of 20%.Keywords: Selection, Decision Support System, Weighted Product, Selection.